The Role of Stakeholders in Sustainable Tourism using Mactor Analysis: Evidence from Kragilan's Top Selfie, Magelang, Indonesia - Evi Gravitiani; Ika Alicia Sasanti; Rebbeca Cindy Sartika; Malik Cahyadin (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2022)
Sustainable tourism development has to pay attention to social, economic, and environmental factors, which is essential in supporting the Sustainable Development Goals (SDGs). The key actors' involvement in tourism development determines its success. This study aims to analyze the strength and convergence between stakeholders or actors who play a role and are involved in the development of Top-Selfie in Kragilan, Magelang, Indonesia, especially from the strategic issues of Increasing Income, Expanding Employment, Increasing Tourists, Poverty Reduction, and Maintaining Local Wisdom, Infrastructure Development, and Pine Forest Conservation. In-depth interviews were conducted with seven important actors, namely (1) The Youth, Sports, and Tourism Office, and (2) the Mount. Merbabu National Park, (3) the village government, (4) the Tourism Awareness Group, (5) Visitors, (6) Local Communities, and (7) Business Actors. The result is the Youth, Sports, and Tourism Offices, Mount. Merbabu National Park and tourism awareness groups are the main actors in developing sustainable tourism in Kragilan's Top Selfie.